Bla ma drag poʼi las byaṅ dṅos grub kun ʼbyuṅ źes bya ba bźugs so - Padma-dkar-po, ʼBrug-chen IV, 1527-1592 (s.n., 1977)
Sādhana focussing upon the practice of the idealized guru in the form of Raudra Kīlaya.